EVALUATING THE MADRASAH LITERACY MOVEMENT AT MAN 2 TIDORE ISLANDS CITY USING THE CIPP MODEL - Rahmawati Ramli; Umar Sulaiman; Saprin; Mardiah Hasan (Academic Bright Collaboration, 2026)
This study aims to evaluate the implementation of the Madrasah Literacy Movement Program (GALATAMA) at MAN 2 Tidore Islands City using the CIPP (Context, Input, Process, Product) evaluation model to assess its institutional alignment and effectiveness. The research adopts a qualitative program evaluation approach. Data were collected through observations, interviews, and documentation involving 15 purposively selected informants (madrasah principal, librarian, teachers, and students). The analysis assesses the alignment in the areas of Qur’anic literacy (BTQ), Arabic, English, and reading culture. Context aligns well with institutional needs and national educational policies. Inputs are structurally adequate, although contemporary non-fiction collections remain limited. The 15-minute reading process is consistently executed but faces operational challenges from digital gadget distractions and varying teacher competencies. Products demonstrate an enhanced madrasah reading culture, improved text comprehension portfolios, and reinforced religious character. This study provides strategic implications for strengthening the management of the Madrasah Literacy Movement. However, this study is limited to one madrasah, so the results are contextual and cannot be generalized widely. This study offers a comprehensive evaluation of GALATAMA using the CIPP framework, uniquely integrating aspects of national policy, multi-linguistic resources, operational implementation challenges, and spiritual character outcomes into a single framework.